2017
DOI: 10.7860/jcdr/2017/26029.10324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Deprivation on the Cognitive Performance of Nurses Working in Shift

Abstract: Cognitive performance was found to be impaired among shift working nurses, due to poor sleep quality and decreased alertness during wake state. Thus, shift work poses significant cognitive risks in work performance of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 27 publications
6
78
0
12
Order By: Relevance
“…It is reasonable to expect that such insufficient rest period between shifts would reduce the chance for nurses to have adequate sleep, and may further increase the fatigue level. Previous studies have shown that the repeated restriction of sleep substantially impairs cognitive performance and decreases alertness during wake hours among shift nurses (Kaliyaperumal, Elango, Alagesan, & Santhanakrishanan, 2017). This is a crucial concern for nurses, given that high levels of cognitive functioning are critical for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to expect that such insufficient rest period between shifts would reduce the chance for nurses to have adequate sleep, and may further increase the fatigue level. Previous studies have shown that the repeated restriction of sleep substantially impairs cognitive performance and decreases alertness during wake hours among shift nurses (Kaliyaperumal, Elango, Alagesan, & Santhanakrishanan, 2017). This is a crucial concern for nurses, given that high levels of cognitive functioning are critical for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation (SD) causes physiological, psychological, and behavioral change (Walker and Stickgold, 2006;Ohayon et al, 2010;Dai et al, 2012), and it especially has an effect on the central nervous system (CNS) (Nabaee et al, 2018). In recent years, the effects of SD on cognitive function have attracted wide attention (Killgore, 2010;Kaliyaperumal et al, 2017;Nasehi et al, 2018). However, the underlying mechanisms of these effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Shift work has significantly changed nurses' sleep patterns. Between 57% and 83.2% (Jafari Roodbandi, Choobineh, & Daneshvar, 2015;Shao, Chou, Yeh, & Tzeng, 2010) of shift nurses worldwide report sleep problems, including sleep disturbances (Hsieh et al, 2011;Reynolds et al, 2016), sleep deprivation (Kaliyaperumal, Elango, Alagesan, & Santhanakrishanan, 2017), and poor sleep quality (De Martino, Abreu, Barbosa, & Teixeira, 2013;Shao et al, 2010;Shu-Hui, Wen-Chun, Mei-Yen, & Jun-Yu, 2014). Sleep deprivation and sleep disturbances have been associated with fatigue (Hughes & Rogers, 2004), chronic diseases, and reduction in health-related quality of life (Asaoka et al, 2013) in shift nurses.…”
Section: Introductionmentioning
confidence: 99%